Total Synthesis of the Antifungal Clinical Candidate ASP2397 Cyclohexapeptide Facilitated by the Chemo-selective Reduction of Secondary N -Benzyloxyamides - Mohamed Osama Ibrahim Mohamed; Yutong Du; Kosuke Ohsawa; Atsushi Tahara; Yoshitaka Shimotai; Hiroshi Hamamoto; A Ganesan; Takayuki Doi (Bulletin of the Chemical Society of Japan, 2026)
Abstract ASP2397 is a siderophore-like cyclic hexapeptide with potent and rapid fungicidal activity against Aspergillus species. We report here its first total synthesis, enabled by an unprecedented one-pot chemoselective reduction of secondary N-benzyloxyamides that strictly preserves the fragile N–O bond. This transformation includes an Ir-catalyzed hydrosilylation with Et2SiH2, followed by NaBH3CN reduction of the resulting oxime derivatives in the presence of a carbamate protecting group and ester, providing efficient access to the non-canonical N-acetyl-N-hydroxyornithine (AhOrn) building block. The macrocycle was assembled via a solid-phase peptide synthesis (SPPS) and head-to-tail macrolactamization. A late-stage one-pot debenzylation/chelation protocol successfully furnished the Al3+-chelated ASP2397. The integrity of the synthesized macrocycle was unequivocally confirmed by its targeted antifungal activity, mirroring the natural product and providing the necessary chemical platform for future structure-activity relationship studies.